Application of Double Hurdle Model on Effects of Demographics for Tea Consumption in China - Lingwen Chen; Xi Guan; Jingying Zhuo; Hua Han; Munishi Gasper; Batoai Doan; Jiangfan Yang; Tzu-Hsing Ko (Journal of Food Quality)
The purpose of this study is to investigate the effects of demographic variables on tea consumption in China. A total of 12,745 samples collected from the China Health and Nutrition Survey in 2011 and a double hurdle model were used to analyze the effects of demographic variables on the extent of tea participation and consumption quantity for men and women. The results of this study indicate that the effects of demographic variables differ between genders in terms of tea participation decisions and consumption quantity decisions. For men, education, family size, region, and employment status were found to exert different effects on participation and consumption quantity decisions; for women, age, education, region, employment status, having elderly individuals in the home, and urbanization exerted different effects on their tea participation and consumption decisions. The most obvious difference between variables affecting men and women pertained to age, family size, and having elderly individuals in the home. The perspectives of each gender, coupled with the double hurdle model used in this study, offer important insights.